JACK BONDURANT’S AMBITION TO MAKE MONEY IN MATT BONDURANT’S LAWLESS - Muhammad Huda; Hilaria Dewi Hapsari (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2021)
This study talks about the ambition of Jack Bondurant to make money as portrayed in Matt Bondurant’s Lawless. It describes and explains how Jack Bondurant’s ambition to make money portrayed in the novel, and it also proves some factors that made Jack so ambitious in being a wealthy money maker. In conducting this study, the writers applied the objective approach as the theoretical approach. The writers used two basic data; primary and secondary data. The primary data was the novel Lawless by Matt Bondurant. The writers collected the data by taking the narrations and dialogues from the book. The data focused on Jack Bondurant’s dialogues, narrations, and acts. Next, the secondary data was taken from the library research, and the writers used descriptive qualitative method to analyze the data. From the analysis, the writers explained that Jack Bondurant was ambitious and had a strong desire to achieve his goals particularly in making more money. His ambition and desire were realized in various spheres of his activities. Jack went to a gangster Floyd Carter’s place to sell his liquor products and he also made a partnership with Floyd Carter. Moreover, the writers found out some factors that caused Jack so ambitious in reaching his goal to make money. They were Jack’s need for recognition from Forrest and Jack’s need for achievement.